Technical cashew nut shell liquid associated with non-protein nitrogen sources in high-grain diets for ruminants: intake and digestibility of nutrients, ruminal fermentation, and microbial protein synthesis - Osmari, Milene Puntel; Branco, Antonio Ferriani; Diaz, Tatiana Garcia; Matos, Laiz Fiorilli de; Goes, Rafael Henrique de Tonissi e Buschinelli; Teodoro, Ana Lúcia (Semina: Ciências Agrárias, 2019)
This study aimed to evaluate the association of technical cashew nut shell liquid (tCNSL) and two sources of non-protein nitrogen (NPN), dry matter intake (DMI), the partial and total apparent digestibility coefficient of nutrients, ruminal fermentation, microbial synthesis, and blood characteristics. Four Holstein steers (438 kg Â± 17.14 kg) fitted with ruminal and duodenal cannula were used. Diets had (in DM basis) 135 g kg?1 of crude protein and 746 g kg?1 of total digestive nutrients. The roughage to concentrate ratio was 30:70. The experimental design was a 4 x 4 Latin square with 14-day experimental periods. The non-protein nitrogen sources used were livestock urea (U) and slow-release urea (SRU) (OptigenÂ® II). The treatments consisted of diets containing U or SRU associated or not with tCNSL. The tCNSL was added to the diet in a proportion of 300 mg kg?1 of concentrate. DMI and ruminal, intestinal and total apparent digestibility coefficients of nutrients were not affected by experimental diets. The association of sources of NPN and tCNSL did not affect pH, ammoniacal nitrogen (NH3-N), plasma urea nitrogen (PUN), and microbial synthesis of animals consuming high-grain diets.